2015
DOI: 10.15740/has/ajbs/10.2/138-142
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of mycopathogensVerticillium lecanii Zimmermen andMetarhizium anisopliae Metchnikoff against sucking pests of Bt cotton

Abstract: Entomopathogenic fungi Verticillium lecanii Zimmermen and Metarhizium anisopliae Metchnikoff have generated a great deal of interest in recent years because of their potential as bio-control component in integrated pest management of cotton. These two mycopathogens were evaluated against sucking pests of Bt cotton during Kharif 2011 and 2012 at Cotton Improvement Project, Mahatma Phule Krishi Vidyapeeth, Rahuri to find out the scope and potentiality of V.lecanii and M.anisopliae against sucking pests of Bt cot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Ghelani et al (2006; found that V. lecanii @ 5 g/ l was effective against Aphis gossypii; and V. lecanii @ 2.5 kg/ ha combined with azadirachtin @ 0.0009% were found moderately effective against major sucking pests of Bt cotton. Raghunandan et al (2018) observed that sucking pests in cotton get reduced significantly with spraying of V. lecanii @ 4 g/ l. Hole et al (2015) observed effectiveness of V. lecanii (2 x 10 12 cfu/g) @ 2000 g/ ha against sucking pests in Bt cotton. Wawdhane et al ( 2020) also observed such effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Ghelani et al (2006; found that V. lecanii @ 5 g/ l was effective against Aphis gossypii; and V. lecanii @ 2.5 kg/ ha combined with azadirachtin @ 0.0009% were found moderately effective against major sucking pests of Bt cotton. Raghunandan et al (2018) observed that sucking pests in cotton get reduced significantly with spraying of V. lecanii @ 4 g/ l. Hole et al (2015) observed effectiveness of V. lecanii (2 x 10 12 cfu/g) @ 2000 g/ ha against sucking pests in Bt cotton. Wawdhane et al ( 2020) also observed such effectiveness.…”
Section: Resultsmentioning
confidence: 99%
“…Bt cotton is highly vulnerable to sucking pests which spread throughout the growing season, as the biotic potential of these sucking pests are high they are potential threat to Bt cotton. Farmers generally use old generation molecules which are hazardous to mammals and ecosystem [6][7][8][9][10][11][12] . Although resistance to neonicotinoids was slow to develop, several insect pests including Aphis gossypii have been shown to possess a potential for resistance development.…”
Section: Introductionmentioning
confidence: 99%